Seasonal Dynamics of Fungi Associated with Healthy and Diseased Pinus sylvestris Needles in Northern Europe - Ahto Agan; Halvor Solheim; Kalev Adamson; Ari Mikko Hietala; Leho Tedersoo; Rein Drenkhan (Microorganisms, 2021)
The relationship between the ecological success of needle pathogens of forest trees and species richness of co-inhabiting endophytic fungi is poorly understood. One of the most dangerous foliar pathogens of pine is Dothistroma septosporum, which is a widely spread threat to northern European forests. We sampled two Pinus sylvestris sites in Estonia and two in Norway in order to analyse the relations between the abundance of D. septosporum and overall fungal richness, specific fungal species composition, time of season, needle age and position in the canopy. In both countries, the overall species richness of fungi was highest in autumn, showing a trend of increase with needle age. The overall species richness in the second-year needles in Estonia and third-year needles in Norway was similar, suggesting that a critical colonization threshold for needle shed in P. sylvestris is breached earlier in Estonia than in Norway. The fungal species richness in P. sylvestris needles was largely affected by Lophodermium conigenum. Especially in older needles, the relative abundance of L. conigenum was significantly higher in spring compared to summer or autumn. The timing of recruitment and colonization mechanisms of different foliage endophytes are shortly discussed.